Exploring Learning Strategies for Kampus Mengajar Students to Catch up with the Conversion Material - Ibrahim, Nuno Heydie; Nuratika, Fauziah Diah; Indriani, Lilia (Metathesis: Journal of English Language, Literature, and Teaching, 2024)
The Kampus Mengajar program plays an important role in education, offering opportunities to develop students outside the regular classroom. However, converting program activities into semester credits has a considerable impact on participants who have to learn independently. The primary goal of this study was to explore what learning strategies are used by Kampus Mengajar 6 & 7 students and the benefits of the learning strategies used by Kampus Mengajar 6 & 7 students. In this study, the researchers used qualitative research. The researchers use interviews as the main instrument to obtain data related to the problems being discussed in this study. The collected data will be analyzed using the descriptive analysis method. Students of Kampus Mengajar 6 and 7 at the English Education Department use learning strategies, such as Social, Cognitive, Affective, and Memory strategies, to catch up with the learning material. In general, Kampus Mengajar students thought their learning strategies worked effectively for understanding the conversion course material. The study examined Kampus Mengajar 6 & 7 English Education students' learning strategies for conversion courses. They primarily used social strategies, such as peer interaction and group discussions, and cognitive strategies, involving critical thinking and problem-solving. Affective and memory strategies were also employed for motivation and retention. Meta-cognitive and compensatory strategies were not used due to insufficient awareness and proficiency.